Kajian Etnobotani Tumbuhan Bungur (Lagerstroemia Speciosa) di Kawasan Hutan Bukit Tamiang Kabupaten Tanah Laut sebagai Buku Ilmiah Populer: (Ethnobotany Study of Bungur (Lagerstroemia speciosa) in Tamiang Hill Forest of Tanah Laut Regency as a Popular Scientific Book) - Siti Muthia Rahmah; Dharmono Dharmono; Aminuddin Prahatama Putra (BIODIK, 2021)
The development of the popular scientific book Ethnobotany of the Bungur plant (Lagerstroemia speciosa) is important because it can raise the local potential of the community in the Bukit Tamiang area and as an enrichment material for the Ethnobotany course in the ULM Biology education program. This study aims to describe the ethnobotany study of Bungur (Lagerstroemia speciosa) in the Bukit Tamiang forest area, Tanah Laut Regency, South Kalimantan and to describe the validity and practicality of the contents of popular scientific books. This method uses two types of research, namely descriptive research, interviews with the public about the Bungur plant and followed by the formative evaluation of the Tessmer test for validation and practicality of the contents of Popular Scientific Books. The results of research on Bungur plants (Lagerstroemia speciosa) in the Bukit Tamiang forest area have various studies including botanical, ethno-ecological, ethno-pharmacological, ethnoanthropological, ethno-economic, and ethno-linguistic studies. The conclusion from the development of a popular scientific book on the study of the ethnobotany of the Bungur plant (Lagerstroemia speciosa) is that expert test results were obtained by two validators with an average value of 90.3% with very valid criteria and the results of the practicality of the content on individual tests by three students getting average results. percentage 3,7% with very good criteria. The advantages of developing a popular scientific book on the ethnobotany study of the Bungur plant (Lagerstroemia speciosa) can be used by students as an enrichment material for Ethnobotany courses and can be read by the wider community because this popular scientific book developed is structured in such a way that it is easily understood by readers. However, the weakness is that the learning material contained in this developed book is insufficient so that further research is needed. Abstrak. Pengembangan buku ilmiah populer Etnobotani tumbuhan Bungur (Lagerstroemia speciosa) penting dilakukan karena dapat mengangkat potensi lokal masyarakat di kawasan Bukit Tamiang dan sebagai bahan pengayaan untuk mata kuliah Etnobotani di prodi pendidikan Biologi ULM. Penelitian ini bertujuan untuk mendeskripsikan kajian etnobotani tumbuhan Bungur (Lagerstroemia speciosa) di kawasan hutan Bukit Tamiang Kabupaten Tanah Laut Kalimantan Selatan dan mendeskripsikan validitas serta kepraktisan isi buku ilmiah popular. Metode ini menggunakan dua jenis penelitian, yaitu penelitian deskriptif wawancara kepada masyarakat tentang tumbuhan Bungur dan dilanjutkan evaluasi formatif uji Tessmer untuk validasi dan kepraktisan isi Buku Ilmiah Populer. Hasil penelitian tumbuhan Bungur (Lagerstroemia speciosa) di kawasan hutan Bukit Tamiang memiliki berbagai kajian diantaranya kajian botani, etno-ekologi, etno-farmakologi, etnoantropologi, etno-ekonomi, dan etno-linguistik. Kesimpulan dari pengembangan buku ilmiah populer kajian etnobotani tumbuhan Bungur (Lagerstroemia speciosa) yaitu didapatkan hasil uji pakar oleh dua validator dengan nilai rata-rata 90,3% dengan kriteria sangat valid dan hasil kepraktisan isi pada uji perorangan oleh tiga mahasiswa mendapatkan hasil rata-rata persentase 3,7% dengan kriteria sangat baik. Kelebihan dari pengembangan buku ilmiah populer kajian etnobotani tumbuhan Bungur (Lagerstroemia speciosa) ini dapat digunakan oleh mahasiswa sebagai bahan pengayaan mata kuliah Etnobotani dan dapat dibaca oleh masyarakat luas karena buku ilmiah populer yang dikembangkan ini disusun sedemikian rupa sehingga mudah dipahami oleh pembaca. Namun, kelemahannya yaitu kurang luasnya materi pembelajaran yang dimuat pada buku yang dikembangkan ini sehingga perlu adanya penelitian lanjutan.